The Effect of Profitability, Leverage, Sales Growth, and Dividend Policy on Tax Avoidance - Andrini, Alifah Dina; Putra, Danang Adi (JOURNAL OF HUMANITIES, SOCIAL SCIENCES AND BUSINESS, 2025)
The main objective of this study was to explore how profitability, leverage, sales growth, and dividend policy impact tax avoidance, as measured by Cash Effective Tax Rate (CETR), while also considering company size as a controlling factor. Secondary data was utilised in a quantitative research approach. The scope of the study included all mining companies listed on the Indonesia Stock Exchange (IDX) between 2021 and 2023. The secondary data was collected from either www.idx.co.id or the companies' official websites. The sampling technique involves purposive selection based on specific criteria to gather 11 sample firms, with Multiple Linear Regression analysis conducted using Eviews 12 software. The study findings indicate that profitability and dividend policy impact tax avoidance, whereas leverage and sales growth do not influence tax avoidance in the mining sector between 2021 and 2023. The study suggests monitoring thriving businesses to verify their compliance with tax regulations. Using debt and boosting sales may not always indicate an intention to evade taxes. Therefore, it is crucial for a company to ensure its dividend policy aligns with tax laws in order to prevent excessive tax avoidance.